2018
DOI: 10.1007/s00420-018-1351-2
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing groups and exploring health differences among multiple job holders aged 45 years and older

Abstract: Purpose To identify distinct groups of older multiple job holders and to explore health differences between these groups. Methods We selected respondents from STREAM, a Dutch cohort study among persons aged 45 years and older, who reported having multiple jobs (N = 702). We applied latent class analysis to identify groups of multiple job holders. The association between these groups and health, measured with the SF-12, was studied cross-sectionally and longitudinally (1 year of follow-up), using linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Furthermore, the vulnerable multiple-job holders more often reported low autonomy and a relatively high percentage of these workers reported that their household was short of money. Cross-sectional analyses showed that the vulnerable group, on average, experienced worse physical and mental health than the three other groups of multiple-job holders (9). In contrast to this vulnerable group of multiple-job holders, other groups of multiple-job holders experienced benefits from holding multiple jobs (9).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Furthermore, the vulnerable multiple-job holders more often reported low autonomy and a relatively high percentage of these workers reported that their household was short of money. Cross-sectional analyses showed that the vulnerable group, on average, experienced worse physical and mental health than the three other groups of multiple-job holders (9). In contrast to this vulnerable group of multiple-job holders, other groups of multiple-job holders experienced benefits from holding multiple jobs (9).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Some part-time workers are precarious although many are not. And as the authors of the letter has shown in their own study; some multiple job holders are precarious while some are not (7).…”
mentioning
confidence: 95%
“…temporary contracts and low job control. These vulnerable multiple job holders experienced worse physical and mental health than the other three groups [17].…”
Section: Introductionmentioning
confidence: 99%
“…To do so, we will study whether differences in health exist between combination multiple job holders and hybrid multiple job holders on the one hand, and single job holders on the other hand? Distinguishing these groups is important since previous research has suggested that combination multiple job holders are overrepresented in groups of multiple job holders that experienced lower physical and mental health [17]. In addition, hybrid MJH may provide employees with better opportunities to combine jobs, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation